The problem of loneliness and coping with stress in the context of life situations experienced by war refugees (based on the research conducted in Rivne, Ukraine) - Petrenko, Oksana; Balika, Liudmyla; Koval, Kateryna (Problem samotności i przezwyciężania stresu w kontekście sytuacji życiowych uchodźców wojennych (na podstawie badań w mieście Równe, Ukraina), 2024)
The article presents the findings of a thorough investigation of the problem of loneliness and coping with stress in the context of life situations experienced by war refugees, based on an empirical study of 304 internally displaced persons (IDPs) in the city of Rivne. The study has shown that IDPs are currently the most vulnerable category of the population due to the following factors: these people have suffered a deterioration of their life quality in terms of the financial and social status which they enjoyed before displacement; they are emotionally unstable and psychologically exhausted as a result of the traumatic war-related events they experienced. Stress, anxiety, fear, and uncertainty have become typical reactions characteristic of displaced persons of any age. The psycho-emotional state of war refugees causes a feeling of alienation, severe stress and loneliness — phenomena that are the result of a number of factors associated with war as one of the most serious crisis situations. As part of the Science for Society II program, the Minister of Education and Science of Poland launched the Faces of Stress and Loneliness in the Context of Military Migration project (November 2023 – March 2024), which envisages conducting a comparative study with the participation of groups of refugees currently living in the cities of Legnica and Krakow (Poland), Drohobych and Rivne (Ukraine). The purpose of the study is to gain an insight into the feeling of loneliness experienced by refugees and internally displaced persons and the coping strategies they use, to determine the level of awareness of global loneliness and its three aspects (emotional, social, existential), to determine the characteristic features of coping strategies used by the respondents in various stressful situations, as well as their long-term and far-reaching social consequences for the further psychosocial functioning of a person in various areas of life. The objectives of the project include determining the possibility of coping with stress by refugees in order to adapt to new circumstances and to continue living an active life under the conditions of war and in the period of transition to peace. A theoretical analysis has been conducted of the phenomenon of loneliness and coping strategies as defined and described in the humanities; the methodology of the research has been substantiated, and the characteristic features of the respondents have been analysed. Based on a statistical analysis of possible loneliness factors and responses to stress, the relationship between socio-demographic and socio-economic variables and stress coping styles has been examined; the link between the feeling of loneliness and stress coping styles has been studied; the hypotheses that the existential face will be predominant among the other faces of loneliness and that war refugees are characterized by differentiated stress-coping styles have been verified. It has been proven that the existential loneliness rate is significantly higher than that of social and emotional loneliness, that is, the dominant face of loneliness is the existential one. As regards the positive statistically significant correlation, it has been found primarily between active and productive/semi-productive coping strategies: the intensity of the task-oriented style differs significantly from that of the emotion-focused and the avoidance-oriented styles. The research data show that the task-oriented style prevails among refugees. The obtained findings necessitated the development of a loneliness and stress coping training program, consisting of 10 sessions, and its implementation in working with war refugees in order to teach them constructive strategies and techniques for coping with stress and the feeling of loneliness under the conditions of reintegration.
Zeszyty Naukowe Collegium Witelona, nr 50(1)/2024, s. 69-96
Keywords: migration; loneliness; stress; war refugees; life situation; migracja; samotność; stres; uchodźcy wojenni; sytuacje życiowe